Study on antibacterial and copper ion removal of chitosan fiber/acetate fiber and yarn for water purification. (December 2021) - Zhang, Yating; Zhang, Shujie; Fu, Lisong; Jing, Mengke
Use chitosan (CS) fiber and cellulose acetate (CA) fiber with different mixing ratios as raw materials, the kinetic and thermodynamic characteristics of the adsorption process of chitosan fiber/cellulose acetate fiber (CS/CA) ratio of 90:10 are explored, and the adsorption process conforms to the quasi-second-order kinetic equation. It can be fitted by Langmuir isotherm. The adsorption process is a spontaneous thermal reaction with both physical adsorption and chemical adsorption. The best adsorption time is 30 min, the time to reach adsorption equilibrium is 180 min, and the best adsorption pH is 5, the most suitable temperature is 35°C, and rising the temperature is conducive to the fibers adsorption. The materials before and after the CS/CA blended yarn adsorbed copper ions were characterized by XRD, DSC, FT-IR, and the adsorption mechanism was analyzed. In the orthogonal experiment, the copper ions concentration has the most obvious effect on the adsorption capacity, and the temperature has the most obvious effect on the adsorption efficiency. The optimal adsorption combination is that the mixing ratio of chitosan fiber/cellulose acetate (CS/CA) is 80:20, the pH is 5, the temperature is 35°C, and the copper ion concentration is 100 mg L −1 . Comparing the adsorption performance of fibers with different mixing ratios, the adsorption performance of CS/CA ratio of 90:10 is the best. The filtration efficiency of the filter material, made of fibers with different mixing ratios, to copper ions is tested, and the filtration performance with a mixing ratio of 90:10 is the best, and the filtration efficiency is 64.33%.